Elastocaloric effect in a Co50Ni20Ga30 single crystal. (15th January 2017) - Shen, Ao; Zhao, Dewei; Sun, Wen; Liu, Jian; Li, Caiju
Abstract: Elastocaloric effect for a Co50 Ni20 Ga30 single crystal has been investigated. A local adiabatic temperature change (Δ T ) of − 6 K was observed on the removal of a uniaxial stress of 150 MPa at 291 K. Infrared thermography measurement reveal a correlated response of martensitic bands and temperature mapping. Both elastocaloric effect and superelasticity exhibit a good reversibility in the 100 times of cycling test. The experimentally obtained Δ T value agrees well with the theoretical one by analyzing the temperature dependence of critical stress based on the Clausius-Clapeyron equation. Graphical abstract: